The Fate of Psychology in Lithuanian Higher Education Institutions during World War II - Rasickaitė, Ignė (Lietuvos istorijos studijos, 2022)
This paper examines the fate of psychology as an academic field of study in Lithuanian universities during World War II. During the period of independent Lithuania, thanks to the first psychologists, psychology existed as a science and found its place in the main and only higher education institution of the time, the Lithuanian University (later – Vytautas Magnus University). After the regaining of Vilnius, some of the psychologists stayed at Vytautas Magnus University and some were transfered from Kaunas to the regained Vilnius University. During World War II, Vytautas Magnus University lost all of its psychologists, and Vilnius University also lost several psychologists. However, even under the conditions of occupation and adverse war conditions, psychology survived at the university. Although psychology established itself as a separate scientific discipline in independent Lithuania, it hadn‘t become one either during the Nazi occupation or the first or second Soviet occupations, instead existing alongside the science of pedagogy in Lithuanian higher education institutions, even with a small group of researchers.
Keywords: psychology; psychology in Lithuania; psychologists; higher education; World War II; Lithuanian University; Vytautas Magnus University; Stephen Batory University; Vilnius University; Vilnius State University